Effects of waterproofing admixture on the compressive strength and permeability of recycled aggregate concrete. (November 2020) - Matar, Pierre; Barhoun, Jean
Abstract: The recycling and reuse of demolished concrete aims to preserve the environment by reducing the waste disposal areas. Moreover, the replacement of virgin aggregates with aggregates obtained by crushing concrete waste can decrease the new quarries development rate. However, the application of recycled concrete aggregates (RCA) in new concretes is generally hindered by the loss of properties of produced concretes. Indeed, the addition of RCA normally affects the concrete properties due to their porosity and weakness. The effectiveness of waterproofing admixtures to improve the durability performance and increase the physical and mechanical properties of natural aggregate concrete (NAC) is well documented in the literature. Yet, the effect of this type of admixture on the properties of concrete incorporating recycled aggregates is not sufficiently studied. This paper investigates some properties of recycled aggregate concrete (RAC) containing waterproofing admixture. Concrete mixes with and without waterproofing admixture are tested in order to examine the slump, temperature, density, and air content of concrete at fresh state, and the compressive strength and permeability of concrete at hardened state. The permeability of concrete is assessed by determining its chloride ion penetration resistance using the rapid chloride permeability test and by measuring the depth of penetration of water under pressure. Test results have shown an improvement of the properties of RAC when waterproofing admixture is added; an improved compressive strength and a decreased permeability of RAC are tangible. Highlights: Properties of RCA with waterproofing admixture were studied. Temperature, density and air content of fresh RAC were not affected by waterproofing admixture. Compressive strength of RAC was enhanced by waterproofing admixture. Waterproofing admixture increased the resistance to chloride ion penetration of RAC and decreased its water permeability. Waterproofing admixture reduced the permeability of RAC.